Procesowe aspekty indywidualnej kontroli abuzywności postanowień umowy — wybrane zagadnienia - Kmiciewicz, Filip (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The study focuses on legal issues occurring in court proceedings regarding the individual examination of the abusiveness of contract terms, which currently result in significant differences incourt decisions, leading to different judgements in similar factual situations, even within one court. The issues discussed could be systematized in the announced regulation of special proceedings with the participation of consumers, increasing the level of consumer protection, standardizing judgments and increasing the level of its predictability.
Keywords: unfair terms; unfair clauses; consumer protection; illegal clauses; individual control of contract provisions